(untitled) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
Following a policy of expansion in the Mediterranean Sea, the United States had developed solid diplomatic and commercial ties with the Kingdom of Naples. This article focuses on the years between the restoration of 1948-49 and the end of the Kingdom of the Two Sicilies in 1861, through the dispatches sent to the Department of State by the U.S. representatives in Naples. The Italian unification aroused interest in the American government and public opinion. The American diplomats experienced the conflict between the need to respect the neutrality in the internal affairs of other nations, the duty to protect the countrymen and defend their country’s interests, and their personal distrust and the antipathy towards the despotic and illiberal governments that pushed them into a spontaneous involvement in the events of the peninsula.